2011
DOI: 10.1038/bjc.2011.421
|View full text |Cite
|
Sign up to set email alerts
|

A person-time analysis of hospital activity among cancer survivors in England

Abstract: Background:There are around 2 million cancer survivors in the UK. This study describes the inpatient and day case hospital activity among the population of cancer survivors in England. This is one measure of the burden of cancer on the individual and the health service.Methods:The national cancer registry data set for England (1990–2006) is linked to the NHS Hospital Episode Statistics (HES) database. Cohorts of survivors were defined as those people recorded in the cancer registry data with a diagnosis of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The range of reported survival periods differed among all the studies, even though all of them included survival of at least 5 years or more. Lu et al [39] included the longest follow-up period (16 years from diagnosis), followed by the studies by Maddams et al [40] and Weaver et al [49] with 16 and 14 years of follow-up, respectively.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…The range of reported survival periods differed among all the studies, even though all of them included survival of at least 5 years or more. Lu et al [39] included the longest follow-up period (16 years from diagnosis), followed by the studies by Maddams et al [40] and Weaver et al [49] with 16 and 14 years of follow-up, respectively.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…[11][12][13] Roder et al 14 describe the role of the cancer register in this type of research as 'the data spine', around which data from other sources are linked to demonstrate patterns of service use in this population. [11][12][13] Roder et al 14 describe the role of the cancer register in this type of research as 'the data spine', around which data from other sources are linked to demonstrate patterns of service use in this population.…”
mentioning
confidence: 99%
“…In recent years, the ability of disease registers to inform health service management and evaluation through linkage with other data sets has been recognized, and internationally, cancer registries have been used extensively to investigate morbidity and health service use in this patient group. [11][12][13] Roder et al 14 describe the role of the cancer register in this type of research as 'the data spine', around which data from other sources are linked to demonstrate patterns of service use in this population. Geographically-defined CP registers are well placed to play such a role in investigating the health service needs of individuals with CP.…”
mentioning
confidence: 99%
“…As Roder et al show in this issue, and has been shown elsewhere in the world, cancer registry data when combined with other administrative or clinical datasets provides the starting point for a variety of different analyses (Maddams et al . ; Mittmann et al . ; Sharpe et al .…”
Section: The Value Of Cancer Registriesmentioning
confidence: 99%
“…As Roder et al show in this issue, and has been shown elsewhere in the world, cancer registry data when combined with other administrative or clinical datasets Correspondence address: Jem Rashbass, Disease Registration, Public Health England, 5th Floor, Wellington House, 133-155 Waterloo Road, London SE1 8UG, UK (e-mail: jem.rashbass@phe.gov.uk). provides the starting point for a variety of different analyses (Maddams et al 2011;Mittmann et al 2014;Sharpe et al 2014).…”
Section: The Value Of Cancer Registriesmentioning
confidence: 99%